Neuroprotection of NAD+ and NBP against ischemia/reperfusion brain injury is associated with restoration of sirtuin-regulated metabolic homeostasis - Wang, Xin-Xin; Mao, Guang-Hui; Li, Qi-Qi; Tang, Jie; Zhang, Hua; Wang, Kang-Lin; Wang, Lei; Ni, Hong; Sheng, Rui; Qin, Zheng-Hong (Frontiers in Pharmacology, 2023)
This study investigated the effects of nicotinamide adenine dinucleotide (NAD+) and butylphthalide (NBP) on ischemic stroke in mice after transient middle cerebral artery occlusion/reperfusion (t-MCAO/R) and cultured primary cortical neurons subjected to oxygen glucose deprivation/reoxygenation (OGD/R). Intraperitoneal injection of NBP within 4 h or intravenous injection of NAD+ within 1 h after t-MCAO/R significantly reduced the volume of infarcts, cerebral edema, and neurological deficits. Administration of NAD+ and NBP immediately after t-MCAO/R in mice showed similar neuroprotection against acute and long-term ischemic injury. Both NAD+ and NBP significantly inhibited the accumulation of MDA and H2O2 and reduced oxidative stress. NAD+ was superior to NBP in inhibiting lipid oxidation and DNA damage. Furthermore, although both NAD+ and NBP improved the morphology of mitochondrial damage induced by ischemia/reperfusion, NAD+ more effectively reversed the decrease of ATP and increase of lactic acid after ischemia/reperfusion compared with NBP. NAD+ but not NBP treatment significantly upregulated SIRT3 in the brain, but the sirtuin inhibitor NAM could abolish the protective effect of NAD+ and NBP by inhibiting SIRT1 or SIRT3. These results confirmed the protective effects of NAD+ and NBP on cerebral ischemic injury. NBP and NAD+ showed similar antioxidant effects, while NAD+ had better ability in restoring energy metabolism, possibly through upregulating the activity of SIRT1 and SIRT3. The protection provided by NBP against cerebral ischemia/reperfusion may be achieved through SIRT1.